The effect of Bonyan-Method Experiential Marathon Structured Groups (BEMSG) on ego functions - Arash Nejatian; Maryam Khaksar; Alireza Zahiroddin; Leila Azimi (Institut Agama Islam Negeri Langsa, 2021)
The present research has studied Bonyan-Method Experiential Marathon Structured Groups' efficacy on the nonclinical populations' ego functions. This study was a quasi-experimental trial with a control group. The trial group participated in the marathon group on three consecutive days (36 hours) and weekly sessions for three weeks. Then the ego function evaluation questionnaire was simultaneously given to both groups. All ego functions in the trial group showed significant growth compared to the control group. Among these, the most remarkable statistical effect size was related to